Designing a ComicQu Application for VIII Graders’ Reading – Writing Assessment - Rahman, Nadya Septiani; Hermayawati, Hermayawati ((JELE) Journal Of English Language and Education, 2019)
This study aimed at producing media that contain the "ComicQu" application as media. This type of research is R&D (Research and Development) using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. In the process of collecting data, several instruments such as interviews, observation, documentation, questionnaires, and tests were employed. The obtained data were analyzed both descriptively and statistically. This research product consisted of a smartphone application with 3 quiz parts and contains 10 questions for each section. Twenty students of the 8th Graders of a State Junior High School in Yogyakarta were involved as the participants. The study revealed that the designed product was appropriate to use as an alternative media for: 1) The product was designed based on the Needs Analysis results; 2) Results on Md (Mean Difference) computation between the average scores of pre-and posttest on the learners’ reading-writing skills showed Md = 78,2 > 63,2 which was considered significantly higher than the demanded school’s KKM (Kriteria Ketuntasan Minimum) or the Minimum Criteria of Learners’ learning Mastery; 3) Expert Judgement also revealed coefficient scores respectively 98.34 from the ELT expert and 78.75 from the IT expert. Thus, it can be concluded that "ComicQu" is appropriately to use as an alternative media to improve the learners’ reading-writing skills of English particularly at the understudied class.